2023
DOI: 10.3126/ijosh.v13i1.43367
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gasoline and Smoking on Lipid Profile and Liver Functions among Gasoline Exposure Workers in Iraq

Abstract: Introduction: The rapid and recent rise in the pandemic of cardiovascular disease implies that the environment plays a significant role. Numerous biological systems, such as the cardiovascular, blood-forming organs, liver, and kidneys, can be affected by gasoline and smoking. Because filling station employees, repair service workers, gasoline truck drivers, and refinery workers are all at a greater risk of being exposed to gasoline fumes. Even though gasoline and smoking have been investigated for so many year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
(25 reference statements)
0
0
1
Order By: Relevance
“…In the same view, Chukwurah et al [18], also observed significantly higher values of HDL-C in rats exposed to premium motor spirit (PMS) for 28 days at 1, 2, and 5 hours daily. However, our finding is contrary to the reports of Mohammed et al [19], who reported a significant increase in plasma HDL-C levels of individuals exposed to gasoline from different derivatives and who were also smoking. They further stated that smoking exacerbated the increases observed in HDL-C plasma concentration.…”
Section: Results Of Lipid Parameters In Control Subjects and Subjects...contrasting
confidence: 99%
“…In the same view, Chukwurah et al [18], also observed significantly higher values of HDL-C in rats exposed to premium motor spirit (PMS) for 28 days at 1, 2, and 5 hours daily. However, our finding is contrary to the reports of Mohammed et al [19], who reported a significant increase in plasma HDL-C levels of individuals exposed to gasoline from different derivatives and who were also smoking. They further stated that smoking exacerbated the increases observed in HDL-C plasma concentration.…”
Section: Results Of Lipid Parameters In Control Subjects and Subjects...contrasting
confidence: 99%